Study on Poverty Alleviation and Tobacco Control in Myanmar - Kyaing, Nyo Nyo (World Bank, Washington, DC, 2013)
This paper looks at tobacco consumption among low-income groups and assesses the level of tobacco-related expenditure among households using tobacco and the opportunity cost of their tobacco expenditure. A survey among tobacco users from low-income groups was conducted to collect data for the analysis. The survey found that households consuming tobacco were spending many times more on tobacco than on health, education and necessities such as clothing and shelter. Tobacco expenditure as a percentage of income was highest among the lowest income groups. The price elasticity estimation results showed a clear negative relationship between prices of tobacco products and their consumption confirming that an increase in prices would efficiently reduce tobacco use.